Antibacterial and wound healing effects of PEG-coated ciprofloxacin-loaded ZIF-8 nanozymes against ciprofloxacin-resistant Pseudomonas aeruginosa taken from burn wounds - Pahlevani, Mohadeseh; Beig, Masoumeh; Barzi, Seyed Mahmoud; Sadeghzadeh, Milad; Shafiei, Morvarid; Chiani, Mohsen; Sohrabi, Aria; Sholeh, Mohammad; Nasr, Shaghayegh (Frontiers in Pharmacology, 2025)
BackgroundAntimicrobial-resistant (AMR) Pseudomonas aeruginosa (P. aeruginosa) poses a significant challenge in burn wound infections due to its biofilm formation and resistance mechanisms, particularly against ciprofloxacin (CIP). Innovative therapies are urgently needed to improve treatment outcomes for burn patients. This study aimed to develop and evaluate Polyethylene glycol (PEG)-Coated CIP-Loaded zeolitic imidazolate framework-8 (ZIF-8) nanozymes (PEG-ZIF-8-CIP) to enhance antimicrobial efficacy against CIP-resistant P. aeruginosa (CRP) and promote wound healing.MethodsClinical isolates of CRP were collected from burn patients and confirmed via polymerase chain reaction for the oprL gene. ZIF-8 nanozymes were synthesized, loaded with CIP, and coated with polyethylene glycol to form PEG-ZIF-8-CIP. These nanozymes were characterized using field emission scanning electron microscopy, Fourier-transform infrared spectroscopy, dynamic light scattering, and zeta potential measurements. Their antimicrobial efficacy, biofilm eradication capability, CIP release, and superoxide dismutase-like activity were assessed; Cytotoxicity Assay and wound healing effects were evaluated in a murine burn model infected with CRP. Statistical analyses were performed using ANOVA with Tukey correction in GraphPad Prism (v10.2.1), considering p-values < 0.05 as statistically significant.ResultsAmong 60 P. aeruginosa isolates, 40 were confirmed as ciprofloxacin-resistant (CRP) and carried the oprL gene. PEG-ZIF-8-CIP nanozymes achieved high drug entrapment efficiency (75%) and strong stability (zeta potential: –31.7 mV), with uniform spherical morphology (∼600 nm). Drug release followed a biphasic pattern—50% released in 6 h, ∼90% by 72 h. The nanozymes showed potent antimicrobial and antioxidant activity, with low MBECs and rapid absorbance reduction. Cytotoxicity was lowest for PEG-ZIF-8-CIP, especially at 24–48 h. In vivo, PEG-ZIF-8-CIP accelerated burn wound healing, reduced inflammation, promoted fibroblast growth and collagen deposition, and achieved the highest bacterial clearance (up to 84%).ConclusionPEG-ZIF-8-CIP nanozymes effectively treated ciprofloxacin-resistant P. aeruginosa in burn-wound models by combining strong antimicrobial and anti-biofilm activity with improved wound healing. Encapsulation in ZIF-8 boosted antibiotic potency, while PEGylation enhanced stability, reduced toxicity, and enabled sustained drug release—highlighting their strong potential for combating antimicrobial-resistant wound infections.